If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + 1 + 3 = 18 Reorder the terms: 1 + 3 + 7n = 18 Combine like terms: 1 + 3 = 4 4 + 7n = 18 Solving 4 + 7n = 18 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 7n = 18 + -4 Combine like terms: 4 + -4 = 0 0 + 7n = 18 + -4 7n = 18 + -4 Combine like terms: 18 + -4 = 14 7n = 14 Divide each side by '7'. n = 2 Simplifying n = 2
| 0.06x+0.05x=0.99 | | (-1/3)t=(4/3) | | K-3/y=6 | | 4.1x+55.6=23.8-11.8x | | 3/4k-6=1 | | 0.09y-0.08y=1.2 | | 2(b+4)=t | | (1/2)R=(5/2) | | 3n-n+7=25 | | 3(8-a)-34=27a-5(2+6a) | | 14x-7y= | | 3=-7-x/2 | | 2/5*4/7 | | -18=(-1/2)y | | 2/4x4/7 | | 13=(-1/6)y | | 100/z-13=7 | | -x+30=-3(6x+7) | | 23=x+43 | | 0.8(6x+7)=2.7-(x-3) | | 5=-2xX+27 | | (1/4)w=16 | | 0.14w=0.70forw | | -5(-3-8x)=15+2x | | 2k-(2.1k-7.5)=28.6 | | x=x+5cosx | | 3x+2x-34+3= | | 2x-4(x-4)=6+3x+12 | | 9x-13=x+5 | | 4(4+4x)=-4+6x | | 2(n-9)=6+n-3(1+n) | | 6ln(x+3)-3lnx= |